Best approximation in metric space for contractive mapping of integral type and Applications of fixed point to Approximation theory (Journal of the College of Basic Education, 2022)
We obtain generalization of best approximation for contractive condition of integral type and we next consider two results on invariant approximation also analyze the existence the application of fixed point and extend some known results of Habinik [7] ,Sahab [10], Kumar [5] Branciari [1], Singh [12].